The power of experiments: How big is your n? - Igor Asanov; Christoph Bühren; Panagiota Zacharodimou (Philipps-University Marburg, School of Business and Economics, 2020)
The replicability and credibility crisis in psychology and economics sparked the debate on underpowered experiments, publication biases, and p-hacking. Analyzing the number of independent observations of experiments published in Experimental Economics, Games and Economic Behavior, and the Journal of Economic Behavior and Organization, we observe that we did not learn much from this debate. The median experiment in our sample has too few independent observations and, thus, is underpowered. Moreover, we find indications for biases in reporting highly significant results. We investigate for which papers and experiments it is more likely to find reporting biases, and we suggest remedies that could help to overcome the replicability crisis.
Keywords: C10; C12; C18; 330; Statistical power; statistical significance; meta-study; balanced randomization; caliper test